PENGARUH SALEP EKSTRAK DAUN WIJAYAKUSUMA (Epiphyllum anguliger (Lem.) G.Don) TERHADAP PENYEMBUHAN LUKA SAYAT TIKUS PUTIH (Rattus norvegicus) GALUR SPRAGUE DAWLEY DAN IMPLEMENTASINYA SEBAGAI MEDIA EDUKASI MASYARAKAT - Rofita Dewi Kartika; Peni Suharti (PEDAGO BIOLOGI, 2017)
Abstract : The aims of this research are: (1) To know the effect of variation concentration of Wijayakusuma leaf extract (Epiphyllum anguliger (Lem.) G.Don) on duration of wound healing on white rats (Rattus norvegicus) Sprague dawley strain; (2) To implement the result of research into the leaflet as a medium of public education. Quantitative research type with post-test group control design method. Samples in this study of white rat (Rattus norvegicus) Sprague dawley strain 2-3 months old with weight 150-200 grams of 24 tails. While research data of wound healing include morphology of mice skin during wound healing, duration of wound healing and measuring the length of closed wound. The sampling technique uses the RAL technique (Completely Randomized Design). The results showed that: (1) There was an effect of giving ointment with variation of leaf extract concentration of Wijayakusuma to rat wound length in rat significantly; (2) There is effect of giving ointment with variation of Wijayakusuma leaf extract concentration on the duration of wound healing in rat significantly; (3) There is effect of giving ointment with variation of Wijayakusuma leaf extract concentration on healing wound on rat significantly; (4) The most effective ointment in wound healing is an ointment of Wijayakusuma leaf extract with a concentration of 40% with an average duration of wound healing time for Â± 7 days; (5) The form of community educational media made from the research is leaflet about ointment leaf extract of Wijayakusuma.